0027 *Developing a simulation ambulance facility and delivering multi-professional high fidelity in-situ simulation across KSS (kent, surrey, sussex). (2nd November 2015) - Staniforth, Matthew; Mackenzie, Matthew; Burden, Rebecca; Hartley, Andrew
Abstract : Background/context: As a result of this project all acute Hospital Trusts within KSS now have the opportunity to run in situ, multi-professional, fully immersive, high fidelity simulation. The project is now live and outcomes are predicted in anticipation for the ASPiH conference in November. Methodology: Funding was sourced from a TEL bid (Technology Enhanced Learning HEE) for the development of a mobile simulation facility with additional support from SECAMB (South East Coast Ambulance). Funding was also provided for regional lead roles from Kent, Surrey and Sussex to drive educational development across the region. The primary aim/outcome was to provide a high quality, multiprofessional, in-situ simulation experience for all Acute Trusts across KSS. Secondary outcomes were to encourage the development of local SBME education by: supporting existing educational programs, to encourage the development of new educational programs within KSS. Description of innovation: The development of a facility in the form of a simulation ambulance. An educational development project available for all health care professionals involved with the Emergency Care Pathway. Results/outcomes: To date the simulation ambulance has visited 40% of Emergency departments within KSS. By November we predict to have visited 100% of departments. The Sim-Ambulance has supported anaesthetic transfer medicine courses, local emergency department and SECAMB simulation development. Improvements/outcomes: The Simulation Ambulance has assisted the development of a framework or standard for Education for the Emergency Care pathway by mapping out the patient experience from start to destination. The initiative has also supported the development of transfer medicine education courses within the region. Conclusions: Successful high profile promotion of high fidelity simulation experience across KSS. Successfully encouraged educational improvement and service development across KSS.